Aggregated demand-side response in residential distribution areas based on tiered incentive prices - Tang, Donglai; Zhang, Qiang; Ma, Tiefeng; Ou, Yuan; Wu, Lei; Tang, Jizhong (Frontiers in Energy Research, 2024)
The residential area refers to the power supply area from distribution transformers to the end users that contains multiple types of flexible resources, such as photovoltaic, energy storage, and power users. Focusing on the challenge of insufficient demand response incentives to multiple types of users in residential distribution areas, a tiered incentive price based demand-side aggregated response method is proposed in this paper. Users in residential distribution areas are classified with an improved k-means clustering method obtain typical types of users. Thereafter, initial scores of users are calculated, and their grades are assigned based on their scores. Corresponding tiered incentive prices are designed for different grades. On this basis, a leader-follower game is proposed to obtain the demand response base price, and tiered incentives are provided to users of different grades to increase their enthusiasm for participating in demand response. In the case study, an actual urban residential distribution area is studied. The results show that the proposed user clustering method has an accuracy of 99.8% in classifying users in a residential distribution area. In addition, the proposed method has a better performance in terms of improving the benefit of the load aggregator and users in the residential distribution area compared with methods such as potential game, hidden Markov, and Monte Carlo. Specifically, from the results, the benefit of load aggregators is increased by 101.96%, 76.07%, and 112.37%, and the income of the users is increased by 54.51%, 36.94%, and 64.91%.